1996
DOI: 10.1200/jco.1996.14.5.1626
|View full text |Cite
|
Sign up to set email alerts
|

Suramin in hormone-refractory metastatic prostate cancer: a drug with limited efficacy.

Abstract: Using this dosing schedule, suramin has limited activity against hormone-refractory metastatic prostate cancer. Recent data suggest that hydrocortisone administered with suramin may be partly responsible for the benefit attributed to the drug. Although a small cohort of patients appeared to benefit, we were unable to confirm the previously reported high rate of activity and durability of remission using this agent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 27 publications
2
13
0
Order By: Relevance
“…Similar results were obtained in another study performed by Dawson et al [9]. Rosen et al [10] reported results on 32 assessable patients with HRPC; 9 patients (28%) had a partial response and they concluded that the combination of suramin and hydrocortisone therapy appears to hold limited activity. More recently, Calvo et al [11] found that a fixed higher-dose suramin schedule showed high, although short-lived, activity and good tolerance profile in HRPC patients.…”
Section: Suraminsupporting
confidence: 77%
“…Similar results were obtained in another study performed by Dawson et al [9]. Rosen et al [10] reported results on 32 assessable patients with HRPC; 9 patients (28%) had a partial response and they concluded that the combination of suramin and hydrocortisone therapy appears to hold limited activity. More recently, Calvo et al [11] found that a fixed higher-dose suramin schedule showed high, although short-lived, activity and good tolerance profile in HRPC patients.…”
Section: Suraminsupporting
confidence: 77%
“…Suramin has been evaluated clinically since the early 1980s. At least 33 trials have been published (e.g., [41][42][43][44][45][46][47][48][49][50]. In all of these trials, suramin was used as a cytotoxic agent at therapeutic plasma concentrations of between 100 and 200 mol/L.…”
Section: Discussionmentioning
confidence: 99%
“…We have established a model of micrometastases to bone and liver in chick embryos using the hormone-independent cancer cell line PC-3 which consistently produces metastases in bone and liver. We used the model to evaluate suramin, a promising agent against hormone-refractory prostate cancer [2, 3, 4], by means of a quantitative PCR assay for micrometastases [5]. …”
Section: Introductionmentioning
confidence: 99%